Role of 18fluorine fluorodeoxyglucose in vulnerable plaque detection for identifying high risk patients - Shaharuddin, Shazreen (2013)
FDG-PET/CT is a combined functional and structural multi modality imaging tool that can be utilized to detect atherosclerotic plaques. This study observed the prevalence of active and calcified plaques in selected arteries during whole-body 18F-FDG PET-CT and correlate the findings with risk factors in coronary artery disease. Beside that, the relationship of active and calcified plaque activity with inflammatory biomarker were determine from the blood marker. The record of 47 patients, which were divided into 17 patients retrospectively and 30 patient prospectively alongside serum inflammatory marker (eg.IL-6 and CRP) and cholesterol (eg lipid profile) undergone whole body FDG PET-CT study in various oncology cases were reviewed. To evaluate the cutoff value for abnormal uptake, retrospective study was conducted to identify patient at risk of developing vascular disease. Mean age was 58±10.3 years old. The presence of 18F-FDG uptake and calcification in selected vascular walls were evaluated. The composition of plaque were recorded using CT value in Housfield unit (HU max). The intensity of 18F-FDG uptake was measured as maximum blood-normalized standardize uptake value (SUVmax). 18F-FDG uptake (SUVmax) and calcification (HUmax) was significantly highest in the carotid walls with (1.91±0.11) and (631.7±215.5) respectively. There was significant relationship between high BMI (overweight) with 18FDG uptake, while calcified artery significant related with hyperlipidemia, diabetes mellitus and hypertension. However the blood marker (such as C-reactive protein) showed significant with high 18FDG uptake and high calcified artery. Beside that, calcified artery showed there was no significant and direct correlation with inflamed vascular wall (SUVmax). This study showed that 18F-FDG PET-CT can be utilized in detecting focal high FDG uptake within vascular plaque in early recognition of high risk patients having coronary artery disease.